Features of seismo-acoustic methods of coal seam faults prediction - Glukhov, O.O.; Pedchenko, M.O.; Borodin, D.S. (Розробка родовищ, 2014)
Seismic-acoustic method to evaluate type and parameters of faults in mined coal seams was developed in the Institute UkrSRSI, NAS Ukraine. The method is based on the usage of computer-aided systems that allow computing and analyzing parameters of seismic wave fields. Developed criteria to identify faultings with using seismic-acoustic method, which are based on the analysis of signal structure, changes in wave train velocity, frequency and amplitude responses and take into account epigenesis stages and structure of coal-bearing strata allow to reveal anomalies with reliability of up to 80 %. В УкрНДМІ НАНУ розроблено сейсмоакустичний метод визначення типу і параметрів порушень вугільних пластів, що відпрацьовуються. Метод базується на використанні комп'ютерних систем, що дозволяють робити розрахунок і аналіз параметрів сейсмічних хвильових полів. Розроблені критерії виявлення аномалій сейсмоакустичним методом, які базуються на аналізі структури сигналу, зміни швидкостей хвильових пакетів, частоти й амплітуди і враховують стадію епігенезу та структуру вуглевмісної товщі, дозволяють виявляти аномалії з надійністю до 80%. В УкрНИМИ НАНУ разработан сейсмоакустический метод определения типа и параметров нарушений отрабатываемых угольных пластов. Метод базируется на использовании компьютерных систем, позволяющих производить расчет и анализ параметров сейсмических волновых полей. Разработанные критерии выявления аномалий сейсмоакустическим методом, которые базируются на анализе структуры сигнала, изменениях скоростей волновых пакетов, частоты и амплитуды и учитывают стадию эпигенеза и структуру углевмещающей толщи, позволяют выявлять аномалии с надежностью до 80%.